2020
DOI: 10.1080/20008198.2019.1705599
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, trauma, fantasy and cognition in dissociative identity disorder, post-traumatic stress disorder and healthy controls: a replication and extension study

Abstract: Background: Two aetiology models for dissociative identity disorder (DID) have been proposed, namely a childhood Trauma Model and an iatrogenic or Fantasy model. A recent study indicated that sleep disturbances underlie dissociative symptomatology. Objective: Our current study aims to test whether this finding can be replicated in an independent sample and to investigate if this finding still holds after correcting for childhood and adult traumatization. An experimental working memory task is included to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 54 publications
0
27
0
1
Order By: Relevance
“…The DID group scored the highest on AF subscale with high endorsements of items relating to sleeping difficulty (endorsed by 82% of the patients). Sleep disruptions could be related to either depression and/or PTSD, both of which are ubiquitous in DID (Boon & Draijer, 1993 ; Brand et al, 2009 ; Putnam, Guroff, Silberman, Barban, & Post, 1986 ; Dimitrova et al, 2020 ). DID individuals also frequently endorsed having low energy (84%) and going to bed to avoid feeling depressed (57%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DID group scored the highest on AF subscale with high endorsements of items relating to sleeping difficulty (endorsed by 82% of the patients). Sleep disruptions could be related to either depression and/or PTSD, both of which are ubiquitous in DID (Boon & Draijer, 1993 ; Brand et al, 2009 ; Putnam, Guroff, Silberman, Barban, & Post, 1986 ; Dimitrova et al, 2020 ). DID individuals also frequently endorsed having low energy (84%) and going to bed to avoid feeling depressed (57%).…”
Section: Discussionmentioning
confidence: 99%
“…Dissociative Identity Disorder (DID) is a disorder characterized by two or more distinct personality states or identities that influence behaviour, accompanied by recurrent amnestic gaps in memory (American Psychiatric Association, 2000 1 ) Figure 1 . Over 95% of these individuals report exposure to early, chronic child maltreatment and adverse early life events, as well as attachment difficulties which has been found to contribute to the development of DID and other trauma-related disorders (Dalenberg et al, 2012 ; Brand et al, 2009 ; Dimitrova et al, 2020 ). Individuals with DID tend to have high scores on many psychological measures’ clinical and validity scales, making it challenging to distinguish genuine versus exaggerated and feigned presentations of DID.…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence that dissociation is at least weakly negatively associated with cognitive control abilities but there is considerable inconsistency in the literature. Some studies have failed to find a relationship between performance-based measures of cognitive control and dissociation (Schurle Bruce, Ray, Bruce, Arnett, & Carlson, 2007;Dimitrova, Vissia, Nijenhuis, Draijer, & Reinders, 2020;Wright, & Osborne, 2005) and others have even found that divided attention and working memory capacity are superior in high relative to low dissociators (De Ruiter, Phaf, Elzinga, & Van Dyck, 2004;De Ruiter, Phaf, Veltman, Kok, & Van Dyck, 2003;DePrince & Freyd, 1999;Elzinga et al, 2007). Also, superior shifting ability has been observed with higher dissociation when controlling for other executive functions (Chui et al, 2016).…”
Section: Dissociation and Cognitionmentioning
confidence: 99%
“…Children and adolescents with functional neurological symptoms have been shown to have poorer performance on a battery of memory and cognitive control tasks relative to healthy control subjects but displayed no difference in intelligence (Kozlowska et al, 2015; see also O'Brien et al, 2015;McWhirter et al, 2020). Some of these inconsistencies are plausibly attributed to many studies not taking adverse life events into consideration (Dimitrova et al, 2020) and/or to the vagaries of the specific tasks used. It is very likely that adverse life events can have deleterious effects on cognition which are independent of the pathological forms of dissociation that they foster (see also Chiu, 2018).…”
Section: Dissociation and Cognitionmentioning
confidence: 99%
“…In this article, the authors report on the validation procedure, reliability and validity of the questionnaire and its discriminating ability to identify individuals with PTSD from individuals with only depression and insomnia, based on pre-sleep thoughts and arousal. As sleep disturbances have been also associated with dissociative symptoms, Dimitrova et al ( 2020 ) investigated the relationship between dissociative symptoms, cognition, fantasy proneness and sleep after controlling for childhood and adult traumatic experiences. The authors concluded that, although patients with dissociative identity disorder and PTSD both report higher levels of sleep disturbances, this association is strictly moderated by traumatic experiences, suggesting no evidence between sleep and dissociative symptoms when traumatizing events were controlled for.…”
Section: In This Issuementioning
confidence: 99%